2018
DOI: 10.1002/slct.201702566
|View full text |Cite
|
Sign up to set email alerts
|

(NH4)2S2O8‐Mediated Direct Oxysulfonyloxylation of Alkynes with Sulfonic Acids to Access α‐Sulfonyloxyketones

Abstract: A novel method for the preparation of a-sulfonyloxyketones via a (NH 4 ) 2 S 2 O 8 -mediated direct oxysulfonyloxylation of alkynes with sulfonic acids is described. This simple yet powerful method allows access to a variety of a-sulfonyloxyketones with a broad substrate scope. Furthermore, under the stipulated conditions, this methodology demonstrates excellent regioselectivity for some 1,2-disubstituted internal alkyne substrates, affording the corresponding a-sulfonyloxyketones in good yields.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Various methods have been reported in the literature for the oxidative α-sulfonyloxylation of ketones but due to few limitations, iodine-mediated oxidation prefer over the others reported procedures. [263][264][265] Therefore, with the importance of α-sulfonyloxyketones in mind, Tongo's group deeply studied the conversion of alkyl arylketones 313 into the corresponding α-sulfonyloxyketones 314 a-i by means of iodine-oxone-MeSO 3 H in a solvent system of MeCN and 2,2,2trifluoroethanolmentioned in moderate to excellent yields (Scheme 104). [266] The detailed mechanism of α-sulfonyloxylation reaction is shown in the Scheme 105.…”
Section: Iodine-inducedα-sulfonyloxylation Of Alkyl Aryl Ketonic Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…Various methods have been reported in the literature for the oxidative α-sulfonyloxylation of ketones but due to few limitations, iodine-mediated oxidation prefer over the others reported procedures. [263][264][265] Therefore, with the importance of α-sulfonyloxyketones in mind, Tongo's group deeply studied the conversion of alkyl arylketones 313 into the corresponding α-sulfonyloxyketones 314 a-i by means of iodine-oxone-MeSO 3 H in a solvent system of MeCN and 2,2,2trifluoroethanolmentioned in moderate to excellent yields (Scheme 104). [266] The detailed mechanism of α-sulfonyloxylation reaction is shown in the Scheme 105.…”
Section: Iodine-inducedα-sulfonyloxylation Of Alkyl Aryl Ketonic Systemsmentioning
confidence: 99%
“…α ‐Sulfonyloxyketones are imperative precursors for the preparation of diverse heteroaromatics such as thiazoles, imidazoles, pyrazoles, oxazoles, imidazo[1,2‐ a ]pyridines, benzofurans, and selenazoles etc. Various methods have been reported in the literature for the oxidative α ‐sulfonyloxylation of ketones but due to few limitations, iodine‐mediated oxidation prefer over the others reported procedures [263–265] . Therefore, with the importance of α ‐sulfonyloxyketones in mind, Tongo's group deeply studied the conversion of alkyl arylketones 313 into the corresponding α ‐sulfonyloxyketones 314 a – i by means of iodine‐oxone‐MeSO 3 H in a solvent system of MeCN and 2,2,2‐trifluoroethanolmentioned in moderate to excellent yields (Scheme 104).…”
Section: Oxidation Of Diverse Functional Groupsmentioning
confidence: 99%
“…However, when we reduced the amount of FeCl 2 to 10 mol%, there was a visible decrease in the yield of 6a (entry 12). Immediately afterwards we tested the effect of the solvent type on the reaction productivity and we found that the yields were reduced (entries [13][14][15][16]. Finally, we explored the amount of H 2 O in the reaction system and discovered that 10.0 equiv.…”
mentioning
confidence: 99%
“…14 The carbon cationic intermediate is quickly converted to enol intermediates VI and XII in the presence of water, which are subsequently converted into the desired products 4a and 6a. 15…”
mentioning
confidence: 99%